Appraisal of Anti-anemic potential of food and synthetic source of iron in women of childbearing age - Abdullah, Muhammad; Ahmed, Zaheer; Mahmood, Shahid; Ahmad, Hajra (Progress in Nutrition, 2021)
Background: Iron deficiency anemia (IDA) is a worldwide public health problem that is most common among females of reproductive age residing in developing countries. Since poverty is the main cause of poor nutritional status, dietary interventions play an imperative role to alleviate such nutritional deficiencies as IDA. Aim: Main objective of present research work was to evaluate the anti-anemic efficacy of natural and synthetic iron sources among women of reproductive age. Methods: In the current study, various treatments composed of natural and synthetic iron sources were urbanized and analysed for proximates, minerals, calorific values and sensory characteristics fortnightly for two months and their effectiveness was checked among anemic non-pregnant women for 90 days. Results: Blood samples of 862 non-pregnant women were collected to investigate their hemoglobin (Hb) status and 36.43 % subjects were scrutinized as anemic (Hb < 11 g/dL). Moreover, blood of these anemic women was investigated further to establish IDA among victims. Hence, 65.92 % non-pregnant females were recognized as IDA prey. At last, 200 volunteers were randomly divided into 4 treatment groups. Conclusions: All treatments except placebo (T0) delivered 9.0 mg of Fe (50 % RDA) among which T2 showed significant variations (P-value